Clinical practice guidelines for the management of children with mother‐to‐child transmitted hepatitis C virus infection. Issue 1 (27th February 2022) - Tajiri, Hitoshi; Bessho, Kazuhiko; Nakayama, Yoshiko; Abukawa, Daiki; Iitsuka, Yoshinori; Ito, Yoshinori; Inui, Ayano; Etani, Yuri; Suzuki, Mitsuyoshi; Takano, Tomoko; Tanaka, Atsushi; Mizuochi, Tatsuki; et al.
Abstract: Background: The first guidelines for care of pregnant women carrying the hepatitis C virus (HCV) and their infants were published in 2005 in Japan. Since then, evidence has gradually accumulated worldwide regarding the natural course and treatment of this condition and, especially in recent years, treatment for chronic hepatitis C in adult patients has made great progress. However, the clinical practice policy for children has not been standardized, and new clinical practice guidelines for children with mother‐to‐child (MTC) transmitted HCV infection have become necessary. Methods: In the development of the current guideline, we requested cooperation from The Japanese Society for Pediatric Infectious Diseases, The Japan Society of Hepatology, and the Japan Society of Obstetrics and Gynecology. The committee members were recommended and approved by each society to participate in developing the guidelines. The guideline was also created in accordance with the Minds Guide for Practice Guideline Development. The statements were prepared by consensus‐building using the Delphi method, based on the comprehensively searched academic papers and guidelines. These articles were retrieved through searching the PubMed, Cochrane Library, and the Igaku Chuo Zasshi databases. Results: Eight clinical questions (CQs) with clinical statements were developed regarding etiology (CQs 1–3), diagnosis (CQs 4 and 5), and treatment (two CQs 6 and 7). In each statement, the consensus rate, evidence level, and recommendation level were determined. Conclusion: The guidelines will be helpful in the management of children with hepatitis C MTC transmission.